Implementation and impact of the global access principles at the University of British Columbia: current successes and future challenges - Gallini, Nancy; Hancock, Robert E. W.; Lester, Richard; Sharp, Brett; Wasan, Kishor M. (Frontiers in Pharmacology, 2023)
In 2007, the University of British Columbia (UBC) was the first university in Canada to establish and adopt global access (GA) principles. Toward implementing these principles, UBC then identified a set of strategies for providing affordable access to new UBC-developed technologies throughout low- and middle-income countries and among vulnerable populations. In this perspective, we provide an update of UBC’s progress over the past 15 years made on several technologies that fall under the GA principles. The technologies reported on are wide-ranging, including an oral medication for the treatment of leishmaniasis; peptides for potential use against malaria, and various bacterial, viral and fungal infections; a portable vaccine cooler; a diagnostic technology to detect severe sepsis; and an SMS Messaging System to monitor and support patients with HIV, TB and COVID-19. We identify challenges faced by the researchers in implementing the GA principles for these technologies and potential solutions for overcoming them through creative licensing and partnerships with public and private sectors, governments, local companies, and communities. As the UBC example illustrates, universities across the globe have an opportunity to make a significant social impact on improving global health of vulnerable populations and on supporting local infrastructures for sustaining these improvements.